Expression of ADRB2 in children with neuroblastoma and its influence on prognosis - Cao, Lijian; Liu, Qingqing; Ma, Yue; Shao, Fengling; Zhao, Zhenzhen; Deng, Xiaobin; Zhou, Jianwu; Wang, Shan (Frontiers in Surgery, 2022)
Abstract Objective Neuroblastoma (NB), originating from sympathetic spinal tissue, is a serious threat to the life of children. Especially in the high-risk group, an overall five-year survival rate less than 50% indicates an extremely poor clinical outcome. Here, the expression the of β-2 adrenergic (ADRB2) receptor gene in tumor tissues of children with NB was detected and the correlation between its expression and clinical characteristics and prognosis was analyzed. Methods Forty-five tumor tissue samples and forty-eight paraffin sections of NB were obtained from Children's Hospital of Chongqing Medical University from 2015 to 2021. Real-time fluorescence quantitative polymerase chain reaction (RT‒qPCR) was utilized to detect the expression of ADRB2 at the mRNA level and immunohistochemistry (IHC) at the protein level. Results For the RT‒qPCR, the analysis showed that the expression of ADRB2 in the high-risk group was significantly lower (P=0.0003); in addition, there were also statistically significant differences in Shimada classification (P=0.0025) and N-MYC amplification (P=0.0011). Survival prognosis analysis showed that the prognosis was better with high ADRB2 expression (P=0.0125), and the ROC curve showed that ADRB2 has a certain accuracy in predicting prognosis (AUC=0.707, CI: 0.530-0.884). Moreover, the expression of ADRB2, N-MYC amplification and bone marrow metastasis were the factors that independently affected prognosis, and at the protein level, the results showed that the differential expression of ADRB2 was conspicuous in risk (P=0.0041), Shimada classification (P=0.0220) and N-MYC amplification (P=0.0166). In addition, Kaplan‒Meier curves showed that the prognosis in the group with high expression of ADRB2 was better (P=0.0287), and the ROC curve showed that the score of ADRB2 had poor accuracy in predicting prognosis (AUC=0.662, CI: 0.505-0.820). Conclusion ADRB2 is a protective potential biomarker and is expected to become a new prognostic biomolecular marker of NB.